2012
DOI: 10.5194/asr-8-45-2012
|View full text |Cite
|
Sign up to set email alerts
|

The historical pathway towards more accurate homogenisation

Abstract: Abstract. In recent years increasing effort has been devoted to objectively evaluate the efficiency of homogenisation methods for climate data; an important effort was the blind benchmarking performed in the COST Action HOME (ES0601). The statistical characteristics of the examined series have significant impact on the measured efficiencies, thus it is difficult to obtain an unambiguous picture of the efficiencies, relying only on numerical tests. In this study the historical methodological development with fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Domonkos et al . () showed that PRODIGE improves the CRMSE by 70% over the raw data. Compared to the truth (a synthetic dataset), the remaining 30% of the CRMSE could not be corrected for by PRODIGE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domonkos et al . () showed that PRODIGE improves the CRMSE by 70% over the raw data. Compared to the truth (a synthetic dataset), the remaining 30% of the CRMSE could not be corrected for by PRODIGE.…”
Section: Discussionmentioning
confidence: 99%
“…The measure of efficiency E is defined as the percentage of the RMSE of the homogenized dataset relative to the RMSE of the raw data (Domonkos et al ., ): E=RMSErawRMSEhomRMSEraw×100. …”
Section: Methodsmentioning
confidence: 99%
“…These spurious signals, called inhomogeneities, can greatly affect climate analysis and should be removed from the time series to the highest possible degree. To meet this criterion, a variety of homogenization methods have been developed in recent decades (Reeves et al , ; Costa and Soares, ; Domonkos et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…As observed temperature time series include five to seven breaks per 100 years on average (Menne et al , ; Venema et al , ), or even more due to hidden short‐term biases (Domonkos, ; Rienzner and Gandolfi, ) multiple break methods are of key importance in providing high level solutions for homogenisation tasks particularly in relation to the homogenisation of temperature. Efficiency tests prove that multiple break methods generally outperform other homogenisation methods (Domonkos, ,; Domonkos et al , ; Venema et al , ). Although some inhomogeneities result in gradually increasing biases instead of abrupt shifts of the means (e.g.…”
Section: Introductionmentioning
confidence: 99%